The Fate of Sediment After a Large Earthquake. Issue 3 (3rd March 2022) - Francis, Oliver; Fan, Xuanmei; Hales, Tristram; Hobley, Daniel; Xu, Qiang; Huang, Runqiu
Abstract: Large earthquakes rapidly denude hillslopes by triggering thousands of coseismic landslides. The sediment produced by these landslides is initially quickly mobilised from the landscape by an interconnected cascade of processes. This cascade can dramatically but briefly enhance local erosion rates. Hillslope and channel processes, such as landsliding and debris flows, interact to influence the total mass, caliber, and rate of sediment transport through catchments. Calculating the sediment budget of an earthquake lends insight into the nature of these interactions. Using satellite imagery derived landslide inventories, channel surveys and a literature review combined with a Monte Carlo simulation approach we present a constrained sediment budget of the first decade after the 2008 M w 7.9 Wenchuan earthquake. With this sediment budget we demonstrate that debris flows are dominant process for delivering sediment into channels and that large volumes of sediment remain in the landscape. In our study area over 88% (469.7 Mega tonnes) of the coseismically generated sediment remains on the hillslopes in 2018. Of the 12% of the sediment that was mobilised, 67% (45.2 ± 22 Mt) was mobilised by debris flows. Despite the large proportion of sediment remaining on the hillslope, the frequency of debris flows declined significantly over our observation period. The reduction in debris‐flow frequency is not correlated to reductions in the frequency of triggering storms, suggesting changes in the mechanical properties of hillslope sediment may drive this observation. The stabilization of coseismically generated sediment greatly extends its residence time and may influence catchment sediment yields for centuries or millennia. Plain Language Summary: Earthquakes produce large volumes of sediment by triggering landslides in mountain ranges. After many earthquakes there is an order‐of‐magnitude increase in erosion rates, however this period of enhanced erosion is short lived. Understanding the processes which control the timespan of the elevated erosion rates and the rates at which they move sediment is vital for determining the continuing impact the earthquake has on a landscape. Using satellite imagery to map and track the movement of sediment after the 2008 Wenchuan earthquake we show that more than 88% (469.7 mega tonnes) of the sediment produced by the earthquake remains on the hillslope after a decade. Debris flows initiating in the landslide deposits are responsible for most of the erosion during this time. The frequency of these flows decreases rapidly after the earthquake indicating the sediment can stabilize quickly. The stabilized sediment could reside in the mountain range for hundreds or thousands of years indicating that it could have a significant impact on erosion rates and landscape evolution. Key Points: More than 88% (469.7 Mt) of sediment produced by the 2008 M w 7.9 Wenchuan earthquake remains on the hillslope 10 years after the event Debris flows rather than fluvially driven erosion are the key process in transporting sediment from the hillslope into the main river Evacuation of landslide deposits is highly stochastic indicating the need for long observation periods to estimate residence time